Determinants of actual and perceived happiness a case of corn farmers of Brgy. Poblacion, Malungon, Sarangani Province - Constantino, Carmela M. (2018)
The subject of happiness and life-satisfaction has been one of the most interesting issues nowadays. With the increase of mental health awareness around the world, people are becoming interested on how happiness would contribute into the development of the society, thus, Bhutan constructed the Gross National Happiness (GNH) as measure of development in the late 1980s. this study aimed to assess the actual and perceived happiness level of a corn farmers base on the 9 domains that were set by GNH in Bhutan and evaluate its possible relationship to the farmer?s sociodemographic profile, farm characteristics, farm inputs, and actions in times of farm failure. This study used the method that Bhutan used in measuring their happiness levels which is the Alkire-Foster Method. To see the relationship of independent variables to happiness, Ordered Logit Regression was used in both actual and perceived happiness models. The result of this showed that only 27 out of 133 respondents are actually happy, while if the respondents were to ask about their happiness level, there would be a total of 84 out of 133 respondents that would say that they are indeed happy. There were 16 significant variables that affects the actual happiness, among the 16 variables for actual happiness level, there only 6 variables that positively affect the actual happiness level of the farmer and these are: age, high school level, high school graduate, technical or vocational for educational attainment, capital, and yield per hectare. While perceived happiness has only 3 significant variables, which are: replanting of crops in time of farm failure, psychological well-being, and ecological diversity and resilience. This study shows that there are many factors that influence happiness, even in farming sector, and it important that the government to support the corn farmer?s education and provide assistance during farm failures to increase the happiness level of farmers.